Prenatal ultrasound phenotypic and genetic etiology of the 17q12 microduplication syndrome - Cai, Meiying; Lin, Min; Guo, Nan; Fu, Meimei; Xu, Liangpu; Lin, Na; Huang, Hailong (Frontiers in Pediatrics, 2022)
Background: Several studies have reported on the clinical phenotype of the 17q12 microduplication syndrome, a rare autosomal dominant genetic disorder, in children and adults, but few have reported on its prenatal diagnosis. This study analyzed the prenatal ultrasound phenotypes of the 17q12 microduplication syndrome to improve the understanding, diagnosis, and monitoring of this disease in fetuses. Methods:A retrospective analysis of 8200 pregnant women who had received an invasive antenatal diagnosis at tertiary referral hospitals between January 2016 and August 2021 was performed. Amniotic fluid or cord blood was sampled from the pregnant women for karyotyping and chromosome microarray analysis (CMA). Results: The CMA revealed microduplication in the 17q12 region of the genome in five fetuses, involving fragments of about 1.5–1.9Mb. Five fetuses with the 17q12 microduplication syndrome had different prenatal ultrasound phenotypes, including duodenal obstruction (two fetuses); mild ventriculomegaly, dysplasia of the septum pellucidum, agenesis of the corpus callosum (one fetus); and a strong echo in the left ventricle only (one fetus). The ultrasound phenotype of one fetus was normal. Among the five fetuses with the 17q12 microduplication syndrome, the parents of three refused pedigree verification, while pedigree verification was performed for the remaining two fetuses to confirm whether the disorder was inherited maternally or paternally, with normal phenotypes. After genetic counseling, the parents of those two fetuses chose to terminate the pregnancy, while the parents of the three unverified fetuses continued the pregnancy, with normal follow-up after birth. Conclusions: Although prenatal ultrasound phenotypes in fetuses with the 17q12 microduplication syndrome are highly variable, our study has highlighted the distinct association between duodenal obstruction and the 17q12 microduplication syndrome. Understanding the relationship between the pathogenesis of the 17q12 microduplicationin prenatal ultrasound phenotypes and its long-term prognosis will contribute to better genetic counseling concerning the 17q12 microduplication syndrome, which is still a challenge.